2021
DOI: 10.1093/nar/gkab531
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical diversity and folding intermediates of parallel-stranded G-quadruplexes with a bulge

Abstract: A significant number of sequences in the human genome form noncanonical G-quadruplexes (G4s) with bulges or a guanine vacancy. Here, we systematically characterized the mechanical stability of parallel-stranded G4s with a one to seven nucleotides bulge at various positions. Our results show that G4-forming sequences with a bulge form multiple conformations, including fully-folded G4 with high mechanical stability (unfolding forces > 40 pN), partially-folded intermediates (unfolding forces < 40 pN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In terms of G4s in the human genome, most G4s are noncanonical structures ( Chambers et al, 2015 ), such as bulged G4s ( Zhang Y. et al, 2021 ), long looped G4s ( Agrawal et al, 2014 ), and vacancy G4s ( Li et al, 2015 ; Wang et al, 2020 ). However, there is little research on the interaction of G4 helicases with these structures.…”
Section: Future Prospectsmentioning
confidence: 99%
“…In terms of G4s in the human genome, most G4s are noncanonical structures ( Chambers et al, 2015 ), such as bulged G4s ( Zhang Y. et al, 2021 ), long looped G4s ( Agrawal et al, 2014 ), and vacancy G4s ( Li et al, 2015 ; Wang et al, 2020 ). However, there is little research on the interaction of G4 helicases with these structures.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Compared to force-clamp experiments, the force-ramp experiments measure the unfolding force distributions in repeating force-ramp cycles with linearly increased forces (constant loading rate), thus allowing measurement of the unfolding forces of stable G4s ( k u ~10 −6 s −1 ). Another advantage in force-ramp experiments is that for sequences that form multiple structures, the distribution of the unfolding forces and unfolding step sizes can provide information of polymorphism of G4s [ 40 , 62 , 79 ]. Figure 3 B shows an example of force-ramp experiments using MT by changing the magnetic field with time.…”
Section: Single-molecule Force Spectroscopy For the Investigation Of G-quadruplexesmentioning
confidence: 99%
“…In 2021, Zhang et al further characterized the mechanical stability of noncanonical parallel-stranded bulged G4s. The results showed that bulged G4s form multiple conformations, including fully folded G4s with an unfolding force peak at >40 pN and partially folded intermediates (guanine-vacancy bearing G4s) with an unfolding force peak at <40 pN [ 62 ]. The effects of bulge lengths, bulge positions, and G-vacancies on the folding rates and folding probability have also been systematically analyzed [ 62 ].…”
Section: Single-molecule Force Spectroscopy For the Investigation Of G-quadruplexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-telomeric GQs have been investigated, too. It has been shown that GQs with bulges and decreased number of quartets are less stable than complete GQs (72). Conversely, increasing K + concentration has been shown to increase the stability of a three- and four-quartet antiparallel bimolecular GQ (73).…”
Section: Introductionmentioning
confidence: 99%